Investigations of mechanical, electronic, and magnetic properties of non-magnetic MgTe and ferro-magnetic Mg0.75TM0.25Te (TM = Fe, Co, Ni): An ab-initio calculation. (20th February 2016) - Mahmood, Q; Alay-e-Abbas, S M; Mahmood, I; Asif, Mahmood; Noor, N A
Abstract: The mechanical, electronic and magnetic properties of non-magnetic MgTe and ferro-magnetic (FM) Mg0.75 TM 0.25 Te ( TM = Fe, Co, Ni) in the zinc-blende phase are studied by ab-initio calculations for the first time. We use the generalized gradient approximation functional for computing the structural stability, and mechanical properties, while the modified Becke and Johnson local (spin) density approximation (mBJLDA) is utilized for determining the electronic and magnetic properties. By comparing the energies of non-magnetic and FM calculations, we find that the compounds are stable in the FM phase, which is confirmed by their structural stabilities in terms of enthalpy of formation. Detailed descriptions of elastic properties of Mg0.75 TM 0.25 Te alloys in the FM phase are also presented. For electronic properties, the spin-polarized electronic band structures and density of states are computed, showing that these compounds are direct bandgap materials with strong hybridizations of TM 3d states and Te p states. Further, the ferromagnetism is discussed in terms of the Zener free electron model, RKKY model and double exchange model. The charge density contours in the (110) plane are calculated to study bonding properties. The spin exchange splitting and crystal field splitting energies are also calculated. The distribution of electron spin density is employed in computing the magnetic moments appearing at the magnetic sites (Fe, Co, Ni), as well as at the non-magnetic sites (Mg, Te). It is found that the p–d hybridization causes not only magnetic moments on the magnetic sites but also induces negligibly small magnetic moments at the non-magnetic sites.